Penerapan Technology Acceptance Model (TAM) Dalam Pengujian Model Penerimaan Sistem Informasi Keuangan Daerah - Fran Sayekti; Pulasna Putarta (Universitas Airlangga, 2016)
This study analyzed the factors which influence the acceptance of the Financial Information System for local Government (SIPKD) using the Technology Acceptance Model (TAM). TAM stated that behavioral intension to use Information System are determined by two beliefs: perceived usefulness (POU) and perceived ease of use (PEU). Perceived usefulness (POU) was defined as the extent to people were sure that the use of the system will improve its performance. Perceived ease of use (PEU) was defined as the extent to people were sure that the system is easy to use. This study analyzed the acceptance SIPKD in the context of the acceptance by the user. User are the local government employee have an obligation to run SIPKD. The analysis focused on the user's perception regarding SIPKD they should run. User perception analyzed is user perception about the ease of use SIPKD and user perceptions about the benefits SIPKD in their work. Research was conducted on the SIPKD in the Special Province of Yogyakarta. Respondents of this study 67 from various agencies in the region of Yogyakarta. The results showed that the Perceived usefulness influence the using of SIPKD, while Perceived Ease of Use does not influence